2017
DOI: 10.1177/0883073816687422
|View full text |Cite
|
Sign up to set email alerts
|

Does Body Mass Index Predict Premature Cardiomyopathy Onset for Duchenne Muscular Dystrophy?

Abstract: Duchenne muscular dystrophy (DMD) leads to cardiomyopathy (CMP). The objective of this study was to estimate the association of body mass index (BMI) with CMP onset. CMP was defined as an LVEF < 55% or LVFS < 28%. Overall, 48% met criteria for CMP. We were unable to demonstrate an association between BMI Z score and age of CMP onset (HR 0.79, 95% CI 0.57 to 1.11, p=0.17) after adjusting for covariates. Duration of corticosteroid use (p=0.01), but not loss of ambulatory ability (p=0.47) was associated with age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…The latter study reported age at LOA by genotype, from 12 years (patients with exon 51 and 53 skip amenable mutations) to 20 years (patients with exon 44 skip amenable mutations). Six studies reported estimates from mixed corticosteroid use samples, and the range was tighter; from 10.0 (range: 4.0–14.0) years (in 67.4% of 85 patients from a single-center chart review) [ 34 ] to 12.4 years (in 64.9% of 225 patients from CINRG) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study reported age at LOA by genotype, from 12 years (patients with exon 51 and 53 skip amenable mutations) to 20 years (patients with exon 44 skip amenable mutations). Six studies reported estimates from mixed corticosteroid use samples, and the range was tighter; from 10.0 (range: 4.0–14.0) years (in 67.4% of 85 patients from a single-center chart review) [ 34 ] to 12.4 years (in 64.9% of 225 patients from CINRG) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage who experienced LOA increased with time (Fig. 2 c) [ 20 , 22 25 , 28 31 , 33 , 34 , 36 , 37 ], from 12.3% at 10 years (from 223 corticosteroid-treated CINRG patients) [ 30 ] to 89.9% at 15 years (from 53 corticosteroid-treated MD STARnet patients) [ 31 ]. Estimates from longitudinal studies report that up to 30% of DMD patients lose ambulation by 10 years (CINRG) [ 28 ], and 90% by 15 years (MD STARnet) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac arrest can occur seven days after CAR-T cell infusion in patients with acute lymphoblastic leukemia (ALL). There have also been reports of a left ventricular ejection fraction that was 25% of the normal baseline [8,87,[96][97][98].…”
Section: Cardiotoxictymentioning
confidence: 99%
“…(BULFIELD et al, 1984;WILLMANN et al, 2012). Entretanto, seu fenótipo é considerado suave, pois sua performance funcional e expectativa de vida é próxima do normal (SICINSKI et al, 1989;DECONINCK et al, 1997;VAN PUTTEN, 2011 A fraqueza muscular inicial leva a criança a ter imperfeições na marcha, no correr, brincar, sentar e levantar e progressivamente por volta dos 12 anos de idade leva ao uso da cadeira de rodas e as disfunções dos músculos axiais resultam em alterações das curvaturas fisiológicas da coluna vertebral, como exemplo o desenvolvimento da escoliose (ARAÚJO et al, 2004;MCKANE et al, 2017).…”
Section: Materials E Métodounclassified
“…A fibrose e necrose do miocárdio resulta-se em cardiomiopatias, a expectativa de vida é severamente reduzida, e a morte súbita ainda pode ocorrer antes dos 20 anos de idade. Em torno da 2ª a 3ª década de vida, estes pacientes necessitam de recursos ventilatórios não invasivos, sendo o comprometimento cardíaco e ou respiratório responsáveis por 80% da causa mortis, devido à insuficiência respiratória sobreposta a um quadro infeccioso e/ou insuficiência cardíaca (CAROMANO, 1999;KORNEGAY et al, 1999;FLANIGAN, 2014;MCKANE et al, 2017). 1998;WILLMANN et al, 2012).…”
Section: Materials E Métodounclassified